If it's not what You are looking for type in the equation solver your own equation and let us solve it.
f(0)=0-9=-9
We move all terms to the left:
f(0)-(0-9)=0
We add all the numbers together, and all the variables
f0-(-9)=0
We add all the numbers together, and all the variables
f+9=0
We move all terms containing f to the left, all other terms to the right
f=-9
| 12-5/4(x+15)=4 | | -2(3y)=-4 | | 7x+43=169 | | D+78=d-234 | | r3=2.25 | | 64-24x=0 | | (X+10/9)+(x+7/3)=7 | | 7+3=(x-4) | | 14r+6=2(5+7r)-4 | | -9=3x/2 | | -x-3+3x=-1 | | 6/7x=1/2 | | m+7m=5+7m-7-5 | | 9=1/2(-2+5n) | | 15(b-2)=90 | | -4/9x=-36 | | 56z=35 | | 25(x-1)^2=49 | | -9/5x=-45 | | 300=0.02v^2+1.2v | | 3+y/3=-1 | | 4(2+x)1=7x-3(x-2) | | 2.5-0.02x=0.08 | | q/6=20 | | (3x+2)+(3x+2) = 8x−2 | | (3x+28)=4(x-10) | | -2x+10=-2(x+5 | | 2y=3.75 | | 12g=12(3/2g−1)+11 | | (x+5)2=10x | | 2/9d+1/9d=3 | | (3x+2)+(3x+2) =8x-2 |